Use of Fungi for Pest Control in Sustainable Agriculture - Keller, Siegfried (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1998)
The registration procedures for microbial pesticides have been based by and large on those developed for registration of chemical pesticides. However, fungi as living organisms differ in many aspects from inert substances. These differences are pointed out and discussed in the light of practical experiences. A pragmatic registration procedure is proposed taking into account the use of a fungus based product in relation to its natural distribution and behaviour. On the one hand, the use of a fungus naturally occurring on the target host does not need a sophisticated registration procedure. On the other hand, however, a genetically altered fungus applied against a non natural host in a non natural habitat needs very careful examination.